2005
DOI: 10.1248/cpb.53.15
|View full text |Cite
|
Sign up to set email alerts
|

Two New Sesquiterpene Lactones from Ixeris chinensis

Abstract: Phytochemical investigation of Ixeris chinensis NAKAI (Asteraceae) has resulted in the isolation of a new guaianolide-type sesquiterpene lactone, ixerochinolide (1) as well as the related glucoside, ixerochinoside (2). In addition, the known guaianolides, 8b b-hydroxy-3-oxo-guaia-4(15),10(14),11(13)-trien-1a a,5a a,6b b,7a aH-12,6-olide (8b b-hydroxydehydrozaluzanin), 8b b,15-dihydroxy-2-oxo-guaia-1(10),3,11(13)-trien-5a a,6b b,7a aH-12,6-olide (lactucin), 3b b,8a a,10a a-trihydroxy-guaia-4(15),11(13)-dien-1a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Compound 7 has also been prepared as an intermediate in the synthesis of plagiochiline N from santonin 23b. Compound 8 was identical with ixerochinoside that was isolated from I. chinensis 12b. Compound 9 was identical with 8-deoxylactucin 24a…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Compound 7 has also been prepared as an intermediate in the synthesis of plagiochiline N from santonin 23b. Compound 8 was identical with ixerochinoside that was isolated from I. chinensis 12b. Compound 9 was identical with 8-deoxylactucin 24a…”
Section: Resultsmentioning
confidence: 98%
“…Studies on some other species of this genus revealed the presence of sesquiterpene lactones such as guaianolides, eudesmanolides, germacranolides, and their glycosides. Because of our interest in the biological activity of sesquiterpene lactones related to the medicinal effects of I. chinensis , we previously isolated three guaianolides ( 1 − 3 ) from this plant . Lee et al and Khalil et al also reported glycosides of guaianolides from this plant . The diverse biological activity reported for guaianolides prompted us to undertake a further investigation of the guaianolides in this plant.…”
mentioning
confidence: 99%
See 1 more Smart Citation